Non-pharmacological Methods Used in the Management of Type 2 Diabetes Mellitus by a Selected Group of People with T2DM in Colombo District, Sri Lanka: A Mixed-Method Study - Lakshani Herath; Manisha Kamalsiri; Perananthan Inthuja; Gayani P Gamage; Dinithi Vidanage (Journal of Diabetology)
Abstract Aims and Objectives: Type 2 diabetes mellitus (T2DM) is one of the most common noncommunicable diseases, which causes high mortality and morbidity among adults. The prevalence of T2DM in Sri Lanka is high due to the unhealthy lifestyles of individuals. Both pharmacological and non-pharmacological interventions are practiced by people with T2DM to achieve better glycemic control. Managing T2DM with non-pharmacological methods is beneficial to both the patients and the country, as they are cost-effective and produce fewer complications. Thus, this study aimed to explore the practice of non-pharmacological methods and associated barriers to adherence in individuals with T2DM who attended the diabetic clinic at a tertiary care facility in Sri Lanka. Materials and Methods: A descriptive cross-sectional study was conducted with both qualitative and quantitative aspects among a conveniently selected 138 individuals with T2DM who attended the diabetic clinic at the University Hospital–Kotelawala Defence University (UH-KDU). Data were collected using an interviewer-administered questionnaire and one-to-one interviews. Gathered data were analyzed by using the SPSS 25.0 version and thematic analysis. Results: The mean age of the participants was 61 (± 10.2) years, and the mean duration of T2DM was 10.1 (±7.9) years. Diet control, exercise, stress management, and adding glucose-lowering food have been identified as the main non-pharmacological methods practiced. Adherence to family meal culture, resistance to follow dietary guidelines, aging, low income, and lack of time were reported by the participants as barriers to adherence. Although males spent more time on exercise compared to females (male vs. female; 36.1 vs. 15.3min, P = 0.025), both groups demonstrated poor glycemic levels (male vs. female; 141.3 ± 52 vs. 136.5 ± 42.2 mg/dl) and higher body mass index (male vs. female; 24.7 ± 4.7 vs. 25.8 ± 4.5 kg/m2). Conclusion: The non-pharmacological practices were not up to the standards of current recommendations for the management of T2DM. Hence, there is a need to improve the motivation of the participants to adapt to a healthy lifestyle.